Enhanced Energy Transfer in Doped Bifluorene Single Crystals: Prospects for Organic Lasers. Issue 4 (13th December 2019) - Baronas, Paulius; Kreiza, Gediminas; Mamada, Masashi; Maedera, Satoshi; Adomėnas, Povilas; Adomėnienė, Ona; Kazlauskas, Karolis; Adachi, Chihaya; Juršėnas, Saulius
Abstract: Organic single crystals with long‐range molecular order ensure enhanced carrier mobility and stability as well as emission outcoupling, which makes them attractive as gain medium for electrically pumped organic lasers. Unfortunately, effects of excitonic coupling introduce losses degrading optical performance in crystals, hence higher lasing thresholds are observed compared to amorphous films. Here, crystal doping strategy is investigated as a method to avoid pronounced reabsorption and annihilation losses associated with J‐type excitonic coupling, while taking advantage of enhanced exciton transport for efficient energy transfer. Bifluorene‐based derivatives linked with acetylene and ethylene rigid bridges are suitable as host and dopant system forming high‐quality crystals doped at various concentrations (0.5–11.0%). Enhanced exciton transport in host crystal mediates picosecond host–dopant energy transfer enabling 100% transfer efficiency at lower doping concentrations compared to amorphous films. Amplified spontaneous emission threshold of 1.9 µJ cm −2 in 3.5% doped crystal is enabled by minimized exciton annihilation and emission reabsorption losses at optimal doping concentration. Abstract : Enhanced exciton transfer in doped crystals is proposed as a mechanism to reduce losses in gain materials. Incorporation of highly emissive dopants into crystals with J‐type excitonic coupling allows to suppress reabsorption and exciton annihilation losses by utilizing long‐range exciton transport. Doped bifluorene crystals show low amplified spontaneous emission threshold of 1.9 µJ cm −2 for organic laser applications.